Risk of latent tuberculosis infection among diabetic patients in Azadi Teaching Hospital, Duhok province: a case control study - Merza, Muayad A; Savo, Abdul Aziz Sulaiman; Jaafer, Muhammad (Asian Journal of Medical and Biological Research, 2018)
Diabetes can be linked with impaired host immunity that subsequently increases the rate of various infections including tuberculosis (TB), particularly in developing countries where TB is endemic. The objectives of this case control study were to determine the prevalence and the risk of LTBI among diabetic patients. It is a prospective case control study conducted in Azadi Teaching Hospital from September 2017 until May 2018. The diabetic patients included in this study were randomly selected. The diagnosis of diabetes mellitus (DM) was made according to the American Diabetes Association (ADA). Diabetes mellitus patients and the control participants were offered a voluntary tuberculin skin test (TST). The TST ≥10 mm was considered positive. The results were analyzed by entering the data in SPSS (statistical package for the social sciences, version 16; SPSS Inc., Chicago, Illinois, USA). Two hundred DM patients and 208 control individuals participated in this study. Collectively, 28 patients had positive TST results. Based on the sputum smear microscopy and CXR, none of these patients showed active TB disease. The differences between the DM patients and the control group had no statistical significance apart from previous hospitalization. The prevalence of LTBI was 23.53% in the diabetic group, whereas, it was 9.62% in the control group. The frequency of LTBI in diabetic patients was significantly higher than the control group. When the diabetic group was compared with the control group in terms of diabetic control and the duration of diabetes disease, there was a statistically significant association of diabetes duration ≥ 10 years and TST positivity. In conclusion, the previous hospitalization was a significant risk factor for diabetic patients to acquire TB bacilli. Latent TB infection was more common in diabetics than non diabetics and there was an increased likelihood of having LTBI with the duration of diabetes ≥ 10 years. To avoid the threatening of TB control program, prophylactic treatment of LTBI in diabetic patients is paramount. Asian J. Med. Biol. Res. June 2018, 4(2): 227-232